KUALITAS PELAYANAN PUBLIK DI KANTOR SATUAN PENYELENGGARA ADMINISTRASI SIM SATLANTAS POLRES TAKALAR - Candra, Siti Widya; Hakim, Lukman; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2025)
This research aims to evaluate the quality of public services for making driving licenses at the Takalar Police traffic police driving license administration unit office by considering analysis of service costs, service facilities and service attitudes. The research method uses a descriptive qualitative approach where data is obtained through interviews, observations and documentation in the field involving various related parties such as traffic police officers and SIM service users who have direct experience with services at the Takalar Police Traffic Unit. The results of the research show that the quality of public services at the Takalar Police traffic police office is influenced by several inhibiting factors such as service costs, service attitudes of officers, inadequate availability of facilities and still need to be improved. In-depth analysis of aspects that provide a comprehensive picture of the quality of public services at the Takalar Police Traffic Unit.